Depression among Elderly people attending at Senior Citizen Home, Bhaktapur - Bhattarai, Bishnu; Poudyal, S (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Introduction: Depression is the most common mental disorder in elderly people. The rapidly increasing growth of elderly population in developing countries including Nepal is at risk of increased population with depression.The objective of this study is to assess the prevalence and level of depression among elderly people attending day care center at Sidhi Saligram Senoir Citizen Home.Methodology: A descriptive cross-sectional study design was carried out among the elderly people attending day care center at Siddhi Shaligram Senior Citizens Home, Bhaktapur. Non-probability convenience time frame sampling technique was used to collect the data. The total sample was112 respondents. Face-to-face interview was carried out using Geriatric Depression Scale Long Form. Data analysis was done with SPSS 16 version and simple descriptive statistics and chi-square were applied for data interpretationResults: The study findings show that the prevalence of depression, i.e. 56.2% had depression. Among the depressed respondents, 77.8% had mild depression and 22.2% had severe depression. Depression among elderly people was found to be significantly associated with the sex (p=0.05) and the presence of chronic illness (p=0.000). However association was not seen among the age, educational level, and marital status, type of family, Income and disability.Conclusion: Prevalence of depression was found high among elderly people. Counseling and group discussion in day care center with psycho social support focused to female suffering from chronic illness is recommended.Journal of Manmohan Memorial Institute of Health SciencesVol. 3, No. 1, 2017, page: 36-44